Use of nanoscale mechanical stimulation for control and manipulation of cell behaviour. (1st April 2016) - Childs, Peter G.; Boyle, Christina A.; Pemberton, Gabriel D.; Nikukar, Habib; Curtis, Adam S.G.; Henriquez, Fiona L.; Dalby, Matthew J.; Reid, Stuart
Graphical abstract: Abstract: The ability to control cell behaviour, cell fate and simulate reliable tissue models in vitro remains a significant challenge yet is crucial for various applications of high throughput screening e.g. drug discovery. Mechanotransduction (the ability of cells to convert mechanical forces in their environment to biochemical signalling) represents an alternative mechanism to attain this control with such studies developing techniques to reproducibly control the mechanical environment in techniques which have potential to be scaled. In this review, the use of techniques such as finite element modelling and precision interferometric measurement are examined to provide context for a novel technique based on nanoscale vibration, also known as " nanokicking ". Studies have shown this stimulus to alter cellular responses in both endothelial and mesenchymal stem cells (MSCs), particularly in increased proliferation rate and induced osteogenesis respectively. Endothelial cell lines were exposed to nanoscale vibration amplitudes across a frequency range of 1–100 Hz, and MSCs primarily at 1 kHz. This technique provides significant potential benefits over existing technologies, as cellular responses can be initiated without the use of expensive engineering techniques and/or chemical induction factors. Due to the reproducible and scalable nature of the apparatus it is conceivable that nanokicking could be used for controlling cell behaviour within a wide array of high throughput procedures in the research environment, within drug discovery, and for clinical/therapeutic applications. Statement of significance: The results discussed within this article summarise the potential benefits of using nanoscale vibration protocols for controlling cell behaviour. There is a significant need for reliable tissue models within the clinical and pharma industries, and the control of cell behaviour and stem cell differentiation would be highly beneficial. The full potential of this method of controlling cell behaviour has not yet been realised.